USING ANIMATED COMET FALL OF 3D MAX 6 Muhammad Zamzami. - Muhammad Zamzami. R; Syahril, SKom Syahril, SKom (Jurnal Sistem Informasi, 2005)
Today technology is growing rapidly which human beings need a lot that can beaccepted and understood by human reason, especially in the world of animation,because animation of a moving image and resembles reality.To the writer want to try to help readers to better know and understand about the fallof a comet, this animation is expected to make readers more satisfied with the readingand can also make the reading to know the form of comets and fall of a comet.